A step toward restoring hand functions in patients with multiple sclerosis—a study protocol - Zoghi, Maryam; Jaberzadeh, Shapour (Frontiers in Rehabilitation Sciences, 2023)
Multiple sclerosis (MS) is a chronic autoimmune disease characterized by inflammation, demyelination of axons, and oligodendrocyte loss in the central nervous system. This leads to neurological dysfunction, including hand impairment, which is prevalent among patients with MS. However, hand impairment is the least targeted area for neurorehabilitation studies. Therefore, this study proposes a novel approach to improve hand functions compared to current strategies. Studies have shown that learning new skills in the motor cortex (M1) can trigger the production of oligodendrocytes and myelin, which is a critical mechanism for neuroplasticity. Transcranial direct current stimulation (tDCS) has been used to enhance motor learning and function in human subjects. However, tDCS induces non-specific effects, and concurrent behavioral training has been found to optimize its benefits. Recent research indicates that applying tDCS during motor learning can have priming effects on the long-term potentiation mechanism and prolong the effects of motor training in health and disease. Therefore, this study aims to assess whether applying repeated tDCS during the learning of a new motor skill in M1 can be more effective in improving hand functions in patients with MS than current neurorehabilitation strategies. If this approach proves successful in improving hand functions in patients with MS, it could be adopted as a new approach to restore hand functions. Additionally, if the application of tDCS demonstrates an accumulative effect in improving hand functions in patients with MS, it could provide an adjunct intervention during rehabilitation for these patients. This study will contribute to the growing body of literature on the use of tDCS in neurorehabilitation and could have a significant impact on the quality of life of patients with MS.